(untitled) (Journal of Environmental Bioremediation and Toxicology, 2025)
Pearl millet (Pennisetum glaucum) and finger millet (Eleusine coracana) are common cereal crops in developing regions; however, their potential is hindered by antinutritional factors, including phytates, tannins, and oxalates, which reduce nutrient bioavailability. This study aimed to assess the impact of natural fermentation on the nutritional and antinutritional properties of these foods, thereby improving their value as dietary staples. Laboratory techniques were employed to analyze changes in proximate composition, vitamins, minerals, and antinutritional factors in fermented and unfermented samples, with the results evaluated using ANOVA (p ≤ 0.05). Natural fermentation led to substantial improvements in nutritional quality. Protein content increased from 11.50% to 13.40% in pearl millet and from 8.70% to 11.30% in finger millet. The mineral content was enhanced, with a rise in calcium levels from 332.00 mg/kg to 344.00 mg/kg in finger millet and in potassium from 240.00 mg/kg to 360.00 mg/kg in pearl millet. Natural fermentation also elevated vitamin E levels, from 0.05 mg/100 g to 0.40 mg/100 g in pearl millet and from 0.32 mg/100 g to 0.30 mg/100 g in finger millet. Antinutritional factors also decreased considerably, with phytates dropping by over 70% in both varieties, alongside marked reductions in tannins and oxalates. A slight carbohydrate reduction, which may be attributed to microbial sugar metabolism, was observed. The findings support fermentation as an accessible and effective method to enhance millet’s nutritional value, providing a sustainable solution to combat malnutrition and improve food security in resource-constrained areas. This research holds significance for nutritionists, food scientists, and policymakers seeking to optimize global dietary quality.